Organic binders for tiling adhesives
By adding an appropriate amount of water dispersible organic binder and porous aluminosilicate compound to the cement-based ceramic tile adhesive, the problem of insufficient mortar performance when using more common and cheaper organic binders in the prior art is solved, and the problem of insufficient mortar performance is achieved. Higher water immersion tensile strength and other performance improvements.
Patent Information
- Application Number
- CN202380051479.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-18
AI Technical Summary
While existing cement-based tile adhesives meet building codes, it is difficult to effectively use more common and cheaper organic adhesives, resulting in insufficient mortar performance.
Add 0.5% to 10% by weight of water dispersible organic binder and 0.05% to 2% by weight of porous aluminosilicate compound to the cement-based ceramic tile adhesive to improve the water-impregnation tensile strength of the mortar and other performance.
By increasing the porous aluminosilicate compound, the water-impregnated tensile strength of the mortar is significantly improved while maintaining other desired properties, solving the problem of insufficient mortar performance when using more common and cheaper organic binders.
Smart Images

Figure BDA0005224933600000121 
Figure BDA0005224933600000141 
Figure BDA0005224933600000151
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cement-based tile adhesives. Background Art
[0002] A tiled surface generally comprises: (a) a substrate, such as a wall or floor, (b) tiles, and (c) an adhesive that bonds the tiles to the substrate.
[0003] In many cases, the adhesive is a cement-based tile adhesive, which is often referred to as mortar. Mortar for tiling typically contains the following dry ingredients mixed with water: (a) a hydraulic binder (also called "cement"), such as Portland cement; (b) an inorganic filler, such as sand; and (c) a water-dispersible organic binder. Some mortars contain additional ingredients, such as cellulose ethers, starch ethers, inorganic or organic fibers, air entraining agents, accelerators, retarders, high-range water reducers, and defoamers.
[0004] Organic binders perform several different functions in mortar. Organic binders increase the tensile and flexural strength of the mortar. Organic binders increase the toughness of the mortar and make it better able to resist cracking caused by temperature changes. Organic binders improve the adhesion of the mortar to the tile and substrate.
[0005] Organic binders are usually sold in the form of "redispersible powders". The redispersible powder usually starts as an emulsion of the organic binder, which can be dried to form a dry powder and then redispersed in water to form an emulsion again. In many embodiments, the redispersible powder contains both an organic binder and a surfactant to help form an emulsion. Examples of organic binder polymers include acrylic copolymers, vinyl ester copolymers, and styrene-butadiene (SB) copolymers. Examples of common vinyl ester copolymers include vinyl acetate-ethylene (VAE), ethylene-vinyl acetate (EVA), and versatate (VEOVA). Examples of surfactants include nonionic surfactants and polyvinyl alcohol.
[0006] Mortars must meet several different building codes that are affected by organic binders. In Europe, the standards are listed in EN 12004. The basic properties that ordinary setting mortars should meet include the following minimum properties:
[0007] Tensile bond strength after storage at room temperature;
[0008] Tensile bond strength after immersion in water;
[0009] Tensile bond strength after heat aging;
[0010] Tensile bond strength after freeze-thaw cycles; and
[0011] ·Opening time
[0012] Typically, the highest degree of performance under these standards requires the use of complex and expensive organic binders, such as terpolymers of ethylene, vinyl acetate and methyl methacrylate. It would be desirable to provide methods of improving the performance of mortars, and particularly mortars using more common and less expensive organic binders. Summary of the invention
[0013] A first aspect of the present invention is an organic binder composition, comprising:
[0014] a) a water-dispersible organic binder suitable for tile mortar; and
[0015] b) 1 to 10 wt % of a porous aluminosilicate compound, based on the weight of the organic binder.
[0016] A second aspect of the invention is a method for preparing mortar using the formulation in the first aspect, wherein the formulation is mixed with cement, filler and water in an amount of 0.5 wt % to 10 wt % (based on the weight of dry ingredients excluding water) to form mortar.
[0017] The third aspect of the present invention is a mortar composition, comprising:
[0018] a) Cement;
[0019] b) Inorganic fillers;
[0020] c) 0.5 to 10% by weight of an organic binder suitable for tile mortar;
[0021] d) 0.05 wt % to 2 wt % of a porous aluminosilicate compound; and
[0022] e) water,
[0023] All weight percentages are based on the weight of dry ingredients (a) to (d) excluding water.
[0024] The fourth aspect of the present invention is a method for adhering a tile to a substrate using the mortar of the third aspect, the method comprising the following steps:
[0025] a) applying the mortar to the substrate;
[0026] b) applying the plurality of tiles to the mortar on the substrate; and
[0027] c) Allow the mortar to set.
[0028] A fifth aspect of the present invention is a tiled surface, the tiled surface comprising:
[0029] a) substrate;
[0030] b) a plurality of tiles; and
[0031] c) a mortar for bonding tiles to a substrate, wherein the mortar comprises: (1) cement, (2) an inorganic filler
[0032] (3) 0.5 to 10 wt % of an organic binder suitable for tile mortar; and (4) 0.05 to 2 wt % of a porous aluminosilicate compound, wherein all weight percentages are based on the weight of components (1) to (4).
[0033] We have found that the presence of a small amount of a porous aluminosilicate compound mixed with the mortar improves the water immersion tensile strength of the mortar while maintaining other desirable properties. In some embodiments, although the present invention also allows the porous aluminosilicate compound and the organic binder to be added separately or mixed with other ingredients, it is convenient to mix the porous aluminosilicate compound and the organic binder before mixing them with the other ingredients in the mortar. DETAILED DESCRIPTION
[0034] The composition of the present invention comprises a water-dispersible organic binder. Typically, the water-dispersible organic binder is in the form of a powder or granules. In some embodiments, the organic binder comprises an acrylic copolymer, a vinyl ester copolymer or a styrene-butadiene (SB) copolymer.
[0035] In some embodiments, the organic binder comprises a vinyl ester copolymer. Examples of suitable vinyl ester copolymers are described in U.S. Pat. No. 6,890,975. In some embodiments, the vinyl ester copolymer is a vinyl acetate-ethylene (VAE) copolymer. In some embodiments, the vinyl ester copolymer is a vinyl ester of versatate (VEOVA) copolymer.
[0036] Vinyl ester copolymers include repeating units derived from one or more vinyl ester monomers, such as vinyl acetate, vinyl n-butyrate, vinyl isobutyrate, vinyl 2-ethylhexanoate, vinyl laurate, 1-methylvinyl acetate, vinyl pivalate, and vinyl esters of C-branched monocarboxylic acids having 9 to 11 carbon atoms, such as vinyl neodecanoate. In some embodiments, the vinyl ester copolymers include vinyl acetate. In some embodiments, the vinyl ester copolymers include both vinyl acetate and vinyl esters of C-branched monocarboxylic acids having 9 to 11 carbon atoms; examples of such polymers are commercially available under the trade name VeoVa.
[0037] In some embodiments, the vinyl ester copolymer further comprises repeating units derived from ethylene or vinyl chloride. For example, the vinyl ester-ethylene copolymer may comprise at least 1 wt % or at least 5 wt % or at least 10 wt % repeating units derived from ethylene, and the vinyl ester-ethylene copolymer may comprise up to 60 wt % or up to 50 wt % repeating units derived from ethylene.
[0038] In some embodiments, the vinyl ester copolymer further comprises repeating units derived from acrylic acid or methacrylic acid esters (such as n-butyl acrylate or 2-ethylhexyl acrylate). For example, the vinyl ester-acrylate copolymer may comprise 30% to 90% by weight of repeating units derived from vinyl esters, 1% to 60% by weight of repeating units derived from acrylates, and 1% to 40% by weight of repeating units derived from ethylene. In some embodiments, the vinyl ester copolymer comprises an acrylate or methacrylate in an amount that cannot be measured.
[0039] The vinyl ester copolymer may also contain a small amount of repeating units derived from ethylenically unsaturated monocarboxylic acids or dicarboxylic acids or their anhydrides, ethylenically unsaturated carboxamides or formonitriles, ethylenically unsaturated sulfonic acids and their salts, and vinyl silanes. Examples of common comonomers in this group include ethylene, acrylic acid, methacrylic acid, acrylamide, acrylonitrile, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tripropoxysilane, vinyl triisopropoxysilane. In some embodiments, the vinyl ester copolymer comprises 0 wt % to 2 wt % or 0 wt % to 1 wt % or 0.5 wt % to 1 wt % of repeating units derived from such comonomers.
[0040] In some embodiments, the organic binder comprises an acrylic copolymer.Examples of acrylic polymers include styrene acrylic polymers such as styrene acrylonitrile copolymer.
[0041] In some embodiments, the water dispersible organic binder has a weight average molecular weight (Mw) of at least 300,000 Da or at least 350,000 Da or at least 400,000 Da. In some embodiments, the water dispersible organic binder has a weight average molecular weight (Mw) of at most 2,000,000 Da or at most 1,500,000 Da or at most 1,200,000 Da.
[0042] In some embodiments, the water-dispersible organic binder has a glass transition temperature of at least -30°C, or at least -20°C, or at least 10°C, or at least 5°C, or at least 15°C. In some embodiments, the water-dispersible organic binder has a glass transition temperature of at most 40°C, or at most 30°C, or at least 25°C.
[0043] In many embodiments, the water-dispersible organic binder further comprises a surfactant. In some embodiments, the surfactant is an anionic surfactant. Examples of nonionic surfactants include nonylphenol ethoxylates and fats (C6 to C 30 ) Alcohol ethoxylates, such as TERGITOL TM 15-S-40 and TERGITOL TM NP10, which are commercially available from The Dow Chemical Company
[0044] In some embodiments, the surfactant is polyvinyl alcohol (PVOH). PVOH is polyvinyl acetate, in which most of the acetate groups have been hydrolyzed to alcohol groups. In some embodiments, PVOH is at least 70% hydrolyzed or at least 80% hydrolyzed or at least 85% hydrolyzed or at least 87% hydrolyzed. In some embodiments, PVOH is at most 95% hydrolyzed or at most 90% hydrolyzed or at most 88% hydrolyzed. In some embodiments, a 4% solution of PVOH in water has a viscosity of at least 2mPa·s or at least 3mPa·s or at least 4mPa·s. In some embodiments, a 4% solution of PVOH in water has a viscosity of at most 40mPa·s or at most mPa·s or at most 26mPa·s. Examples of suitable PVOH have a weight average molecular weight (Mw) of at least 15,000 or at least 20,000. Examples of suitable PVOH have a weight average molecular weight (Mw) of at most 150,000 or at most 120,000. Examples of suitable PVOH include PVOH 04-88 and PVOH 26-88, which are commercially available.
[0045] In some embodiments, the organic binder and the surfactant are selected so that the organic binder forms an emulsion with a particle size of at least 200 nm, or at least 400 nm, or at least 500 nm, or at least 600 nm. In some embodiments, the organic binder and the surfactant are selected so that the organic binder forms an emulsion with a particle size of at most 1000 nm, or at most 800 nm.
[0046] In some embodiments, the organic binder and surfactant are selected so that the organic binder forms an emulsion that is stable in a cohesive environment. The cement used in the mortar creates an alkaline environment high in calcium ions. This environment can cause some emulsions to decompose. Other combinations of organic binders and surfactants are known to form stable emulsions in this environment, and combinations that form stable emulsions can be advantageously used in the mortars of the present invention.
[0047] It should be understood that the nominal dry powder may contain a small amount of moisture. In some embodiments, the water-dispersible organic binder comprises no more than 5 wt % or no more than 4 wt % or no more than 3 wt % or no more than 2 wt % or no more than 1 wt % moisture. In some embodiments, the water-dispersible organic binder may not contain detectable moisture (0 wt %).
[0048] Examples of suitable water-dispersible organic binders are commercially available, such as those sold under the trade name DOW TM LatexPowder 2000 and DOW TM Latex Powder 2001, and under the trade names VaVeova and VaE-Veova. Other water-dispersible organic binders can be prepared by emulsion copolymerization of vinyl ester monomers and ethylene monomers in aqueous dispersions according to known methods, such as described in Lindmann, Vinyl Acetate / Ethylene Emulsion Copolymers, Paint Manufacture, September 1968, 30-36, and in U.S. Pat. No. 5,576,384 and U.S. Application No. 2009 / 0069495A1. The resulting dispersion can be spray dried to produce a redispersible powder.
[0049] The composition of the present invention further comprises a porous aluminosilicate compound.
[0050] In some embodiments, the porous aluminosilicate compound has at least or at least or at least In some embodiments, the porous aluminosilicate compound has an average pore size of at most or at most or at most or at most or at most The average pore size.
[0051] In some embodiments, the porous aluminosilicate compound has a diameter of at least 5 cm 3 / g or at least 10cm 3 In some embodiments, the porous aluminosilicate compound has an average pore volume of at most 60 cm 3 / g or up to 40cm 3 The average pore volume of / g.
[0052] In some embodiments, the porous aluminosilicate compound has at least 100 m 2 / g or at least 200m 2 / g or at least 300m 2 / g or at least 400m 2 / g or at least 500m 2 / g Brunauer-Emmett-Teller (BET) surface area. In some embodiments, the porous aluminosilicate compound has a surface area of at most 2000 m 2 / g or up to 1500m 2 / g or up to 1000m 2 / g or up to 800m 2 / g or up to 600m 2 / g of BET surface area.
[0053] In an embodiment, the porous aluminosilicate compound may have a Si / Al molar ratio of 1 to 1000. All individual values and subranges of the molar ratio of 1 to 1000 are disclosed and included herein, including 1 to 100, 1 to 200, 1 to 300, 1 to 400, 1 to 500, 1 to 600, 1 to 700, 1 to 800, 1 to 900, 100 to 1000, 200 to 1000, 300 to 1000, 400 to 1000, 500 to 1000, 600 to 1000, 700 to 1000, 800 to 1000, or 900 to 1000.
[0054] Examples of suitable porous aluminosilicate compounds include zeolites, feldspars, sodalites, and octahedral coordinated aluminum, such as andalusite, kyanite, and sillimanite. In certain embodiments, the porous aluminosilicate compound is a zeolite.
[0055] In some embodiments, the zeolite has a silica to alumina ratio (SiO2 / Al2O3) of at least 1, or at least 1.5, or at least 1.7, or at least 1.8, or at least 1.9, or at least 2. In some embodiments, the zeolite has a silica to alumina ratio (SiO2 / Al2O3) of at most 10, or at most 5, or at most 3, or at most 2.5, or at most 2.3, or at most 2.2.
[0056] In some embodiments, the zeolite has a static water adsorption capacity (at 25°C and 50% relative humidity) of at least 15 wt%, or at least 18 wt%, or at least 20 wt%, or at least 21 wt%. In some embodiments, the zeolite has a static water adsorption capacity (at 25°C and 50% relative humidity) of at most 50 wt%, or at most 35 wt%, or at most 30 wt%, or at most 25 wt%.
[0057] In some embodiments, the zeolite is a class A zeolite or a class X zeolite. Examples of suitable class A zeolites include 3A, 4A, and 5A zeolites. Examples of suitable class X zeolites include 13X zeolite. In some embodiments, the zeolite includes 4A zeolite.
[0058] Suitable zeolites are commercially available, such as under the trade name Siolite. Other zeolites are available in nature or can be prepared by known methods, such as described in Introduction to Zeolite Science and Practice - 3rd Revised Edition (J H. et al.-eds.) Chapter 3 (Synthesis of Zeolites by Jihing Yu).
[0059] In some embodiments, the weight ratio of the porous aluminosilicate compound to the organic binder (both dry) is at least 1 wt % or at least 2 wt % or at least 2.5 wt % or at least 3 wt % or at least 4 wt % or at least 5 wt %. In some embodiments, the weight ratio of the porous aluminosilicate compound to the organic binder (both dry) is at most 10 wt % or at most 9 wt % or at most 8 wt % or at most 7 wt % or at most 6 wt % or at most 5 wt %.
[0060] In some embodiments, the porous aluminosilicate compound and the organic binder are added separately to the mortar. One or both of the organic binder and the porous aluminosilicate compound can be mixed into the cement or filler or water alone or together before mixing the full mortar, or the other ingredients can be mixed together first, and the organic binder and / or the porous aluminosilicate compound can be added later.
[0061] In some embodiments, it may be convenient to mix the organic binder and the porous aluminosilicate compound together before adding them to the remaining mortar to form the organic binder composition.
[0062] Optionally, the organic binder composition may comprise further additives, such as the additives for mortar mentioned below or further emulsifiers or emulsion stabilizers, such as polyvinyl alcohol or anti-caking and flow aids such as kaolin, calcium carbonate or silica.
[0063] In some embodiments, the organic binder composition may be premixed with cement or other additives for mortar to form a masterbatch containing a high concentration of the organic binder composition. The masterbatch may then be mixed with the remainder of the mortar to achieve the desired concentration of the organic binder composition.
[0064] The organic binder and the porous aluminosilicate compound are added together or separately to the mortar containing cement and inorganic filler.
[0065] ASTM recognizes five types of cement: Type 1 (ordinary Portland cement); Type 2 (medium sulfate-resistant cement); Type 3 (fast-hardening cement), Type 4 (low-heat cement), and Type 5 (high sulfate-resistant cement). Any of these cements can be used in mortar. In some embodiments, the cement is ordinary Portland cement. In some embodiments, the cement is a variant of ordinary Portland cement, known as white cement. In some embodiments, the cement contains less than 25% by weight, or less than 20% by weight, or less than 15% by weight, or less than 10% by weight, or less than 5% by weight, or substantially 0% by weight of high-alumina cement. Suitable cements are commercially available.
[0066] The mortar should contain enough cement to be effective as a tile adhesive. In some embodiments, the mortar contains at least 5 wt % cement, or at least 10 wt % cement, or at least 15 wt % cement, or at least 20 wt % cement, or at least 22 wt % or at least 25 wt % or at least 28 wt % or at least 30 wt % based on the dry ingredients in the composition (and excluding water). In some embodiments, the mortar contains up to 60 wt % or up to 50 wt % or up to 45 wt % or up to 40 wt % or up to 35 wt % cement, based on the dry ingredients in the composition (and excluding water).
[0067] Examples of inorganic fillers include silica sand, quartz sand, kaolin, calcium carbonate, magnesium carbonate, talc, or mixtures thereof. Suitable inorganic fillers are commercially available.
[0068] In some embodiments, the mortar comprises at least 25 wt % or at least 30 wt % or at least 35 wt % or at least 40 wt % or at least 45 wt % filler, based on the dry ingredients in the composition (and excluding water). In some embodiments, the mortar comprises at most 95 wt % or at most 90 wt % or at most 85 wt % or at most 80 wt % or at most 75 wt % or at most 70 wt % or at most 65 wt % or at most 60 wt % filler, based on the dry ingredients in the composition (and excluding water).
[0069] In some embodiments, the mortar further comprises a pozzolan, such as fly ash, calcined kaolin, pumice or fumed silica. In some embodiments, the mortar comprises at least 5 wt % or at least 10 wt % or at least 15 wt % of a pozzolan. In some embodiments, the mortar comprises at most 50 wt % or at most 40 wt % or at most 30 wt % of a pozzolan. Pozzolans and their use in mortars and concretes are well known and are described in U.S. Pat. No. 9,181,131 B2.
[0070] In addition to cement and fillers, some embodiments of the mortar may optionally include other ingredients such as cellulose ethers, starch ethers, inorganic or organic fibers, air entraining agents, accelerators, retarders, high-range water reducers, and defoamers.
[0071] Cellulose ethers (such as methyl cellulose, ethyl cellulose and methylethyl cellulose) can increase the water retention of the mortar and extend the open time. Suitable cellulose ethers are commercially available, such as under the trade name WALOCEL TM or METHOCEL TM .
[0072] Starch ethers (such as hydroxypropyl starch ether) can improve the anti-sagging and anti-slip properties of the mortar, as well as extending the open time and providing a smoother surface. Suitable starch ethers are commercially available, such as under the trade name Aqualon.
[0073] Fibers added to the mortar can improve its tensile strength. Examples of fibers include steel fibers, glass fibers, polymer fibers (such as polypropylene or polyester), and natural fibers. In some embodiments, the fibers are chopped prior to addition, such as to a length providing an aspect ratio of 30 to 150. Suitable fibers are commercially available.
[0074] • Air entraining agents form small air bubbles in the mortar, which improves its resilience during freeze-thaw cycles. Air entraining agents are usually surfactants. Suitable air entraining additives are commercially available.
[0075] Accelerators speed up the setting of mortar. They can be particularly useful in cold weather applications. Examples of common accelerators include calcium nitrate, calcium nitrite, calcium formate, and certain aluminum compounds. Accelerator formulations with instructions for use are commercially available.
[0076] • Retarders slow the setting time of the mortar. Examples of common retarders include lignin sulfonic acid, hydroxycarboxylic acids (such as hydroxy acid), carbohydrates, lead oxide, zinc oxide, phosphates, borates, and calcium, sodium, and ammonium salts of fluoride. Retarder formulations with instructions for use are commercially available.
[0077] Superplasticizers allow the production and use of mortars with lower water content. Examples of superplasticizers include sulfonated melamine-formaldehyde condensates, sulfonated naphthalene-formaldehyde condensates, modified lignin sulfonates, and polycarboxylates. Superplasticizer formulations with instructions for use are commercially available.
[0078] Defoamers reduce air entrapment and voids in mortar. Examples of defoamers include mineral
[0079] Oils, polyethylene glycols and polyether siloxanes. Defoamers are commercially available with instructions for use.
[0080] In some embodiments, the mortar comprises at most 20 wt % or at most 10 wt % or at most 5 wt % or at most 2 wt % of other ingredients, based on the dry ingredients in the composition (and excluding water). In some embodiments, the mortar comprises an unmeasurable amount of other ingredients (substantially 0 wt %) or at least 1 wt % or at least 2 wt %, based on the weight of the dry ingredients in the composition (and excluding water).
[0081] When used, cement, filler, organic binder, porous aluminosilicate compound and other ingredients (if any) are thoroughly mixed with water.
[0082] In some embodiments, the amount of organic binder is at least 0.5 wt % or at least 1 wt % or at least 1.5 wt % or at least 2 wt % based on the weight of the dry ingredients in the composition (excluding water). In some embodiments, the amount of organic binder is at most 10 wt % or at most 8 wt % or at most 6 wt % or at most 5 wt % based on the weight of the dry ingredients in the composition (excluding water).
[0083] In some embodiments, the amount of porous aluminosilicate compound is at least 0.01 wt % or at least 0.02 wt % or at least 0.05 wt % or at least 0.08 wt % or at least 0.1 wt % based on the weight of the dry ingredients in the composition (and excluding water). In some embodiments, the amount of porous aluminosilicate compound is at most 2 wt % or at most 1.5 wt % or at most 1 wt % or at most 0.75 wt % or at most 0.5 wt % or at most 0.3 wt % or at most 0.25 wt % based on the weight of the dry ingredients in the composition (and excluding water).
[0084] The optimum amount of water varies according to the ingredients and their intended use, and can be easily determined by experiment. In some embodiments, the amount of water is at least 20% by weight, or at least 22% by weight, or at least 24% by weight, or at least 26% by weight of the dry ingredients. In some embodiments, the amount of water is at most 60% by weight, or at most 50% by weight, or at most 40% by weight, or at most 30% by weight of the dry ingredients.
[0085] In some embodiments, the amount of water is selected to provide a mortar (when wet) that is sufficiently fluid so that it can be smoothly applied to the substrate, and sufficiently viscous so that it holds the tile to the substrate without excessive sliding or falling of the tile before the mortar sets. In some embodiments, the mortar has a viscosity of at least 400 Pa·s, or at least 450 Pa·s, or at least 500 Pa·s, or at least 525 Pa·s, or at least 550 Pa·s. In some embodiments, the mortar has a viscosity of at most 800 Pa·s, or at most 700 Pa·s, or at most 650 Pa·s, or at most 600 Pa·s.
[0086] In one embodiment, the finished product is a mortar comprising:
[0087] a) Cement;
[0088] b) Inorganic fillers;
[0089] c) 0.5 to 10% by weight of an organic binder;
[0090] d) 0.05 wt % to 2 wt % of a porous aluminosilicate compound; and
[0091] e) water,
[0092] All weight percentages are based on the weight of dry ingredients (a) to (d) excluding water.
[0093] The mortar may also optionally contain 0 to 20 wt % of other additives as previously described. The selection and amount of each ingredient may optionally reflect the embodiments and examples discussed previously.
[0094] Among other uses, mortar can be used for ordinary tile laying. First, the mortar is applied to the substrate. Second, the tile is pressed onto the applied mortar. Third, the mortar is allowed to set. Each of these steps is well known and has been practiced for thousands of years.
[0095] Examples of suitable substrates include any known rigid building material, such as drywall, wood, plaster or concrete. Examples of suitable tiles include any known tiles, such as ceramic, glass, porcelain, stone or marble, terracotta or concrete.
[0096] The average thickness of the mortar varies according to many factors, such as the smoothness of the substrate and the tile and the intended use. In some embodiments, the mortar is applied with a thickness of at least 2 mm, or at least 3 mm, or at least 4 mm (when wet). In some embodiments, the mortar is applied with a thickness of at most 8 mm, or at least 6 mm, or at least 5 mm (when wet). Solidification causes the mortar to shrink. In some embodiments, the solidified mortar is at least 1 mm, or at least 1.25 mm, or at least 1.5 mm thick. In some embodiments, the solidified mortar is at most mm, or at most 4 mm, or at most 3 mm thick.
[0097] The setting time of the mortar depends on many factors, such as temperature, water content, and mortar composition. In some embodiments, the setting time is between 300 minutes and 700 minutes. In some embodiments, the setting time may be longer or shorter.
[0098] In some embodiments, the mortar provides at least 0.5 N / mm after storage at room temperature. 2 or at least 0.75N / mm 2 or at least 1N / mm 2 or at least 1.2N / mm 2 or at least 1.4N / mm 2 or at least 1.45N / mm 2 There is no maximum desired tensile adhesion, but in many embodiments, it is higher than 3 N / mm 2 or 2N / mm 2 The adhesion provides little added value.
[0099] In some embodiments, the mortar provides at least 0.5 N / mm 2 or at least 0.6N / mm 2 or at least 0.7N / mm 2 or at least 0.8N / mm 2 or at least 0.9N / mm 2 or at least 0.95N / mm 2 or at least 1N / mm 2 There is no maximum desired water-immersion tensile adhesion, but in many embodiments, it is higher than 2 N / mm 2 or 1.5N / mm 2 The adhesion provides little added value.
[0100] In some embodiments, the mortar provides at least 0.5 N / mm 2 or at least 0.75N / mm 2 or at least 1N / mm 2 or at least 1.2N / mm2 or at least 1.4N / mm 2 or at least 1.6N / mm 2 or at least 1.7N / mm 2 There is no maximum expected heat aged tensile adhesion, but in many embodiments, it is higher than 3 N / mm 2 or 2.5N / mm 2 The adhesion provides little added value.
[0101] In some embodiments, after an open time of 20 minutes (as defined in EN 12004), the mortar provides a strength of at least 0.5 N / mm 2 or at least 0.75N / mm 2 or at least 1N / mm 2 or at least 1.2N / mm 2 or at least 1.4N / mm 2 or at least 1.6N / mm 2 or at least 1.8N / mm 2 or at least 1.9N / mm 2 There is no maximum expected tensile bond for this test, but in many embodiments, it is higher than 3N / mm 2 or 2.5N / mm 2 The adhesion provides little added value.
[0102] In some embodiments, after an open time of 30 minutes (as defined in EN 12004), the mortar provides a strength of at least 0.5 N / mm 2 or at least 0.7N / mm 2 or at least 0.9N / mm 2 or at least 1.2N / mm 2 or at least 1.28N / mm 2 or at least 1.4N / mm 2 or at least 1.6N / mm 2 There is no maximum expected tensile bond for this test, but in many embodiments, it is higher than 3N / mm 2 or 2N / mm 2 The adhesion provides little added value.
[0103] The method produces a tiled surface comprising:
[0104] a) substrate;
[0105] b) a plurality of tiles; and
[0106] c) a mortar for bonding tiles to a substrate, wherein the mortar comprises: (1) cement, (2) an inorganic filler
[0107] (3) 0.5 to 10 wt % of an organic binder suitable for tile mortar; and (4) 0.05 to 2 wt % of a porous aluminosilicate compound, wherein all weight percentages are based on the weight of the dry ingredients (1) to (4).
[0108] The selection and specific embodiments of the substrate, tile and mortar are as previously described, except that the mortar has been allowed to set so that it no longer contains high levels of water in the wet mortar. The proportions of the dry ingredients are as previously described.
[0109] Example
[0110] Test Method
[0111] The parameters described in this application can be measured using the following measurement methods:
[0112]
[0113] Molecular weight
[0114] The Mark-Houwink plots of molecular weight / molecular weight distribution and branching structure analysis were measured using triple detector gel permeation chromatography. The methods and formulas used are described in U.S. Patent No. 8,871,887. U.S. Patent No. 8,871,887 is incorporated herein by reference. For gel permeation chromatography (GPC) methods (conventional GPC, light scattering (LS) GPC, viscometric GPC, and gpcBR), a triple detector gel permeation chromatography (3D-GPC or TDGPC) system was used. The system includes a Robotic Assistant Delivery (RAD) high temperature GPC system [other suitable high temperature GPC instruments include Waters (Milford, Mass.) Model 150C High Temperature Chromatograph; Polymer Laboratories (Shropshire, UK) Model 210 and Model 220; and Polymer Char GPC-IR (Valencia, Spain)], equipped with a Precision Detectors (Amherst, Mass.) two-angle laser light scattering (LS) detector Model 2040, an IR4 infrared detector from Polymer ChAR (Valencia, Spain), and a 4-capillary solution viscometer (DP) (other suitable viscometers include Viscotek (Houston, Tex.) 150R4-capillary solution viscometer (DP)). A GPC having at least one of these latter two independent detectors and the former detector may be referred to as a "3D-GPC" or "TDGPC", while the term "GPC" alone generally refers to a conventional GPC. Data collection is performed using software (eg, Polymer Char GPC-IR). The system is also equipped with an online solvent degasser (eg, from Polymer Laboratories).
[0115] The eluent from the GPC column set flows through each detector arranged in series in the following order: LS detector, IR4 detector, followed by DP detector. The systematic method for determining multi-detector offset is similar to that of Balke, Mourey et al. (Mourey and Balke, Chromatography Polym., Chapter 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym., Chapter 13, (1992)). Olexis LS columns are used. The sample transport chamber is operated at 140°C and the column chamber is operated at 150°C. The sample is prepared at a concentration of 0.1 grams of polymer in 50 milliliters of solvent. The chromatographic solvent and sample preparation solvent are 1,2,4-trichlorobenzene (TCB) containing 200 ppmw of 2,6-di-tert-butyl-4-methylphenol (BHT). The solvent is purged with nitrogen. The polymer sample is gently stirred at 160°C for four hours. The injection volume is 200 microliters. The flow rate through the GPC was set to 1 mL / min.
[0116] For conventional GPC, an IR4 detector is used, and the GPC column is calibrated by running 21 narrow molecular weight distribution polystyrene standards. The molecular weight of the standards ranges from 580 g / mol to 8,400,000 g / mol, and the standards are contained in six "mixed liquid" mixtures. Each standard mixture is at least ten steps apart between individual molecular weights. Polystyrene standards are prepared under the following conditions: for molecular weights equal to or greater than 1,000,000 g / mol, 0.025 g is prepared in 50 mL of solvent, and for molecular weights less than 1,000,000 g / mol, 0.05 g is prepared in 50 mL of solvent. The polystyrene standards are dissolved at 80 ° C by gentle stirring for 30 minutes. The number average molecular weight, weight average molecular weight, and z average molecular weight are calculated according to formulas, for example, as described in U.S. Patent No. 8,871,887.
[0117] For LS GPC, a precision detector PDI2040 detector model 2040 is used. For 3D-GPC, the absolute weight average molecular weight is calculated according to the formula, for example, as described in U.S. Patent No. 8,871,887. The gpcBR branching index is determined by calibrating the light scattering, viscosity and concentration detectors and subtracting the baseline. The integration window is set for the integration of the low molecular weight retention volume range in the light scattering and viscometer chromatograms, and the chromatogram indicates the presence of detectable polymers from the refractive index chromatogram. Linear polyethylene standards are used to establish polyethylene and polystyrene Mark-Houwink constants. This constant is used to construct two linear reference conventional calibrations of polyethylene molecular weight and polyethylene intrinsic viscosity as a function of elution volume, for example, as described in U.S. Patent No. 8,871,887. In order to determine the gpcBR branching index, the light scattering elution area of the sample polymer is used to determine the molecular weight of the sample. The final Mark-Houwink constant is used for analysis, for example, as described in U.S. Patent No. 8,871,887.
[0118] Example
[0119] A series of dry mortars were prepared by mixing the ingredients listed in Table 1. In the case of Inventive Examples 1 and 2, all ingredients in the composition were mixed together to prepare the mortar. In the case of Inventive Examples 3 to 6, an organic binder polymer was mixed with zeolite to form a redispersible powder composition. The redispersible powder composition was further mixed with other mortar ingredients to prepare the mortar.
[0120] Comparative Examples A and B were prepared using the procedure of Example 2, but without the use of zeolite.
[0121] The compositions of Table 1 were thoroughly mixed with the water listed in Table 2, and the mortar viscosity, wet mortar density, tensile bond strength after storage at room temperature, tensile bond strength after immersion in water, tensile bond strength after heat aging, tensile strength after 20 minutes and 30 minutes of airing, and setting time were tested using the test methods listed above. The results of each test are listed in Table 2. Each mortar was classified according to EN 12004 and is listed in Table 2.
[0122] Table 1
[0123]
[0124]
[0125] *TDCC = The Dow Chemical Company All amounts in Table 1 are in weight percent.
[0126] Table 2
[0127]
Claims
1. An organic binder composition, comprising: (a) a water-dispersible organic binder suitable for use in tile mortars; and (b) 1 to 10 wt % of a porous aluminosilicate compound, based on the weight of the organic binder. 2 . The organic binder composition according to claim 1 , wherein the water-dispersible organic binder comprises a polymer having a glass transition temperature of −20° C. to 30° C. 3 . The organic binder composition according to claim 1 , wherein the water-dispersible organic binder comprises a vinyl ester copolymer.
4. The organic binder composition according to claim 1, wherein the water-dispersible organic binder comprises a vinyl acetate-ethylene copolymer. The organic binder composition according to claim 1 , wherein the porous aluminosilicate compound is zeolite.
6. The organic binder composition according to claim 5, wherein the porous aluminosilicate compound has to The average pore size. 7 . The organic binder composition according to claim 5 , wherein the porous aluminosilicate compound is a type A zeolite or a type X zeolite.
8. A method of using the organic binder composition according to claim 1, wherein the organic binder composition according to claim 1 is mixed with cement, filler and water in an amount of 0.5 wt% to 10 wt% based on the weight of dry ingredients excluding the water.
9. A mortar, comprising: (a) Cement; (b) inorganic fillers; (c) 0.5 to 10% by weight of an organic binder suitable for tile mortar; (d) 0.05 wt % to 2 wt % of a porous aluminosilicate compound; and (e) water, All weight percentages are based on the weight of dry ingredients (a) to (d).
10. The mortar according to claim 9, wherein the organic binder is a vinyl ester copolymer.
11. The mortar according to claim 9, wherein the porous aluminosilicate compound has to The average pore size of the zeolite.
12. The mortar according to claim 9, wherein the porous aluminosilicate compound is a type A or type X zeolite.
13. The mortar according to claim 9, wherein the mortar has a strength of at least 1 N / mm2 after immersion in water in the test of European standard EN 12004. 2 tensile bond strength.
14. The mortar according to claim 9, wherein the mortar has a strength of at least 1.28 N / mm2 after 30 minutes of exposure in the test of European standard EN 12004. 2 tensile bond strength.
15. A method of adhering a tile to a substrate using the mortar according to claim 9, the method comprising the steps of: (a) applying the mortar to a substrate; (b) applying a plurality of tiles to the mortar on the substrate; as well as (c) allowing the mortar to set.
Citation Information
Patent Citations
Coating Compositions Having High Weathering Resistance, Process for Preparation Thereof and Use Thereof
US20090069495A1
Low-emission dispersion paints, coating materials and synthetic resin dispersion plasters as well as processes for the preparation thereof
US5576384A
Water-redispersible polymer powders for building adhesive compositions
US6890975B2
Ethylene-based polymers and processes to make the same
US8871887B2
Redispersible powder composition for dry mortar formulations
US9181131B2